Implementation Of Single Sign-On Method in E-Inventory System of Harapan Medan University - Tantri Hidayati Sinaga (JAICT, 2019)
Maintenance of lecturing instruments is very important to ensure that every inventory works well to support the continuity of the teaching and learning process. Control activities must be carried out at any time so that it can speed up the handling process to improve inventory services. The purpose of this study was to utilize the lecture instrument inventory data to make an electronic inventory system application (e-inventory) of the lecture instruments that would be used to record the inventory of lecture instruments by applying the multi-user concept using the Single Sign On method. Implementation of Single Sign On in application development is intended to maximize performance because each job will be carried out by multi-users, easily controlled because each user has different access rights and is more efficient in terms of accountability. This study will produce a Lecture Instrument E-Inventory System equipped with Single Sign On facilities so that it will be easier to apply. The results of this study can be developed by adding supporting facilities to applications that have been made in accordance with the standard procedure for recording lecture instruments so that they can be applied in many universities.Maintenance of lecturing instruments is very important to ensure that every inventory works well to support the continuity of the teaching and learning process. Control activities must be carried out at any time so that it can speed up the handling process to improve inventory services. The purpose of this study was to utilize the lecture instrument inventory data to make an electronic inventory system application (e-inventory) of the lecture instruments that would be used to record the inventory of lecture instruments by applying the multi-user concept using the Single Sign On method. Implementation of Single Sign On in application development is intended to maximize performance because each job will be carried out by multi-users, easily controlled because each user has different access rights and is more efficient in terms of accountability. This study will produce a Lecture Instrument E-Inventory System equipped with Single Sign On facilities so that it will be easier to apply. The results of this study can be developed by adding supporting facilities to applications that have been made in accordance with the standard procedure for recording lecture instruments so that they can be applied in many universities.